ANALISIS TEORI KONFLIK: STRATEGI NEGOSIASI SEBAGAI SOLUSI EFEKTIF DALAM MANAJEMEN ORGANISASI DI SD IT AN-NAHAR - Muslim, Khidayat; Prayoga, Hade Yustika (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
Conflict within organizations is an inevitable phenomenon, including in educational environments such as SD IT An-Nahar. Conflicts may arise from various factors, such as differences in perceptions, goals, or interests among teachers, staff, parents, and students. This study aims to analyze the conflicts occurring at SD IT An-Nahar using a conflict theory approach and to explore negotiation strategies as an effective solution for managing these conflicts. The research employs a qualitative method with interviews, observations, and documentation as data collection techniques. The findings reveal that conflicts at SD IT An-Nahar predominantly stem from communication gaps, misaligned expectations, and limited resource allocation. Collaborative negotiation strategies prove to be an effective approach to conflict resolution, yielding win-win solutions that strengthen interrelations among stakeholders. This study underscores the importance of negotiation skills training for all stakeholders in the school to foster a harmonious working environment and support the achievement of educational objectives.